2023
DOI: 10.1002/fsn3.3243
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fresh mango consumption on gut health and microbiome – Randomized controlled trial

Abstract: Some individual fruits have been widely researched for their effects on overall health and correlations with chronic diseases. The beneficial effects of mango supplementation on metabolic diseases have been detected. However, research into mango consumption on gut health, including the microbiome, is limited to processed mango preparations or peels. Our goal was to examine the effects of fresh mango consumption on the gut microbiome, gut permeability proteins, and bowel movement habits in overweight/obese indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Corynebacterium are gram-positive bacilli, including many toxigenic species which cause respiratory tract infections such as diphtheria [ 70 ]. A recent study has reported that fresh fruit consumption, especially mangoes can increase the abundance of Corynebacterium pyruviciproducens which is considered as immune modulator [ 71 ]. Erysipelotrichaceae_UCG-003 increased with pickle, rice and fresh fruits consumption and is previously observed to be enriched with high fiber diet intake [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corynebacterium are gram-positive bacilli, including many toxigenic species which cause respiratory tract infections such as diphtheria [ 70 ]. A recent study has reported that fresh fruit consumption, especially mangoes can increase the abundance of Corynebacterium pyruviciproducens which is considered as immune modulator [ 71 ]. Erysipelotrichaceae_UCG-003 increased with pickle, rice and fresh fruits consumption and is previously observed to be enriched with high fiber diet intake [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corynebacterium are gram-positive bacilli, including many toxigenic species which cause respiratory tract infections such as diphtheria (70). A recent study has reported that fresh fruit consumption, especially mangoes can increase the abundance of Corynebacterium pyruviciproducens which is considered as immune modulator (71). Erysipelotrichaceae_UCG − 003 increased with pickle, rice and fresh fruits consumption and is previously observed to be enriched with high ber diet intake (72).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a 12-week crossover design study, 27 participants consumed 100 kcal/day of either mangos or low-fat cookies with a washout period of 4 weeks. Interestingly, mango consumption increased the abundance of Prevotella maculosa , Corynebacterium pyruviciproducens , and Mogibacterium timidum while decreasing the abundance of Prevotella copri [ 83 ]. Prevotella copri has been shown to be increased in subjects with psoriasis; thus, it will be interesting to evaluate whether mango consumption could have a beneficial effect on psoriasis and other skin diseases [ 84 ].…”
Section: Association Between Plant-based Diet Alternatives and Gut Mi...mentioning
confidence: 99%